Enzymatic hydrolysis of bitter sorghum for bioethanol production - Deenanath, Evanie Devi (My University, 2010)
The production of bioethanol derived from biomass and fermentation is becoming increasingly popular due to the application in the motor-fuel industries. The present work, therefore aimed to investigate level of bioethanol produced from bitter sorghum grains by the use of commercial exogenous enzymes and to evaluate the microbial quality of sorghum processing. A temperature-programmed mashing regime was carried out using a dual-enzyme combination of Cerezyme Sorghum and Fungamyl 800L for the hydrolysis of sorghum starch. Subsequently, bioethanol was produced by fermenting the hydrolyzate with either Saccahormyces cerevisiae strain NRRL Y2084 or Issatchenkia orientalis. HPLC analyses of the hydrolyzates showed the presence of fructose, glucose and maltose. This indicated that bitter sorghum grains can be converted to fermentable sugars using these particular enzymes. Both yeast species are capable of fermenting the available sugars, producing 7% (v/v) of alcohol. At the post-mashing stage, no microbial contaminants were found to be associated with the process. At the post-fermentation stage, plate counts showed microbial counts between 5.00-8.00 Log cfu/mL. The characterization of microbes isolated at the postfermentation stage was based on PCR amplification of the 16S and ITS regions. iii Following sequencing, the isolates were identified as Lactococcus lactis, Lactcoccus garvieae, Lactobacillus casei, Enterococcus faecalis, Saccharomyces cerevisiae strains NCL117 and T8, Saccharomyces paradoxus, Saccharomyces pastorianus, Saccharomyces kudriavezvii, Issatchenkia orientalis and Candida inconscipua. Fermentation conditions were favourable for the survival of these MOs.